2022
DOI: 10.1155/2022/2382535
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple Theories Based Determinants and their Causal Relationships Affecting the Adoption of Community Cloud in Saudi HEI

Abstract: The higher education institutions (HEIs) are adopting the new modern cloud computing technique rapidly due to its cost effectiveness, efficient and productive feature. Though cloud computing technology is beneficial to educational sector, it is important to assess their economic benefits, technical, organizational, environmental appropriateness and potential obstacles before adopting the new technology. There are four evaluating theory for adopting the cloud computing technology which are the Technology Organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…TOE Theory incorporates technology-organization, environment, and sociocultural elements to provide a comprehensive explanation of the possibility of a specific corporation adopting new technology. These three traits are shared by both the restrictions that operate as barriers and the opportunities that act as accelerators for technological growth, according to the TOE paradigm (Aldahwan & Ramzan, 2022). Conversely, DOI theory, which focuses on how people embrace new ideas, has made substantial use of this technique.…”
Section: Research Model and Hypothesmentioning
confidence: 99%
See 3 more Smart Citations
“…TOE Theory incorporates technology-organization, environment, and sociocultural elements to provide a comprehensive explanation of the possibility of a specific corporation adopting new technology. These three traits are shared by both the restrictions that operate as barriers and the opportunities that act as accelerators for technological growth, according to the TOE paradigm (Aldahwan & Ramzan, 2022). Conversely, DOI theory, which focuses on how people embrace new ideas, has made substantial use of this technique.…”
Section: Research Model and Hypothesmentioning
confidence: 99%
“…These functionalities enable students to efficiently organize and manage their files and documents on mobile devices (Almaiah & Al Mulhem, 2019). In contrast, extensive research conducted in the past decade has revealed that perceived ease of use plays a substantial role in influencing the intention to use a system, either directly or indirectly through its impact on perceived usefulness (Aldahwan & Ramzan, 2022). When a system is easy for users to interact with, they are more likely to perceive it as useful and express an intention to use it (Jaradat et al, 2020).…”
Section: Research Model and Hypothesmentioning
confidence: 99%
See 2 more Smart Citations
“…The research shows that the community cloud computing technology provides significant benefits to higher education institutions, but that a centralized, well-structured system is required. In addition, they developed a framework to study the factors that influence the adoption of community cloud computing in Saudi HEIs [ 21 ].…”
Section: Literature Reviewmentioning
confidence: 99%